Static and Dynamic Measurement of Ocular Surface Temperature in Dry Eyes - Li Li Tan; Srinivasan Sanjay; Philip B. Morgan (Journal of Ophthalmology)
Purpose. To study ocular surface temperature (OST) in dry eyes by static and dynamic measures. Methods. OST was recorded on 62 dry eyes and 63 age- and sex-matched controls. Static measures were study of absolute OST at t=0, 5, and 10 s after eye opening. Dynamic measures were study of mean change and net change in OST over 10 s of sustained eye opening. Ten OST indices studied were temperatures of the geometric center of the cornea (GCC), extreme temporal (T1) and nasal conjunctiva (T4), midtemporal (CT) and nasal conjunctiva (CN), temporal (LT) and nasal (LN) limbus, and mean (MOST), maximum (Max T), and minimum (Min T) temperatures of the region of interest. Results. For static measures, dry eyes recorded significantly lower GCC, MOST, Min T, Max T, T4, CT, LT, LN, and CN. For dynamic measures, dry eyes had significantly steeper regression line of mean change (corresponding to greater net change) for Max T 5 s onward and T4 at 3 s onward. Conclusions. Both static and dynamic measures of the OST were valuable and can be used as clinical tool to assess dry eye.